1998
DOI: 10.1007/s005200050206
|View full text |Cite
|
Sign up to set email alerts
|

An open-label dose comparison study of ondansetron for the prevention of emesis associated with chemotherapy prior to bone marrow transplantation

Abstract: Nausea and vomiting are significant side effects in bone marrow transplant (BMT) patients who receive high-dose preparative regimens. Higher than conventional ondansetron doses and continuous infusion might improve emetic control, because of the high doses and combinations of chemotherapy (CT) used in this setting. Our objective was to conduct a prospective, randomized study comparing two different administration methods of high-dose ondansetron during a BMT preparative regimen in breast cancer patients. Patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Another study analysing intermittent versus continuous ondansetron in 66 patients undergoing autologous transplants for breast cancer found no difference in the outcome: emesis control was not statisfactory. 10 Good acute control but with late-onset delayed emesis With a combination of oral granisetron, oral prochlorperazine and oral dexamethasone, Frakes et al…”
Section: Resultsmentioning
confidence: 99%
“…Another study analysing intermittent versus continuous ondansetron in 66 patients undergoing autologous transplants for breast cancer found no difference in the outcome: emesis control was not statisfactory. 10 Good acute control but with late-onset delayed emesis With a combination of oral granisetron, oral prochlorperazine and oral dexamethasone, Frakes et al…”
Section: Resultsmentioning
confidence: 99%
“…Outside of the HSCT setting, numerous studies have concluded that these agents provide equivalent control of N/V induced by highly emetogenic chemotherapy when administered at equipotent doses. [2][3][4][5][6][7][8] Although three of these agents have been extensively studied in HSCT patients over the last 8 years, [9][10][11][12][13][14][15][16][17][18][19][20][21][22][23] limited data directly comparing these agents is available. [21][22][23] Ondansetron, the first 5-HT 3 receptor antagonist approved in the United States, has been the most widely studied and is most effectively used in combination with corticosteroids for prevention of CINV; granisetron's effects are also enhanced with the use of corticosteroids.…”
mentioning
confidence: 99%
“…19 For patients receiving high-dose chemotherapy or chemo/ radiotherapy regimens in association with hematopoietic stem cell support, a number of studies suggest that antiemetic control may be a greater challenge in this setting. 17,[20][21][22][23][24][25] In the current prospective trial, we have clearly demonstrated that despite the use of standard prophylactic treatments, antiemetic control is indeed suboptimal for patients receiving allogeneic or autologous hematopoietic stem cell transplants and appears to be inferior to the results obtained with standard-dose chemotherapy. Limitations of the study include the diverse conditioning regimens, antiemetic treatments, and small sample size.…”
Section: Discussionmentioning
confidence: 81%